A Sociolinguistic Study of the Functions of Swear-Words Used by Motivator Gary Vaynerchuk in the Video Titled The World is Abundant, Stop Holding Yourself Back | London Keynote 2021 - Kenny John Anderson Prayogo; Jusuf Imam Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study examines the functions of swear-words by motivational speaker Gary Vaynerchuk, using Holmes’ (2013) social factors and Ljung’s (2011) swear words functions theory. The qualitative method was applied to textual data from 26 units of Gary Vaynerchuk's speeches, identifying 76 swear-words in the video. These words, often found in intimate conversations in American society, follow specific patterns and are used as slot-fillers within sentence structures to emphasize Gary Vaynerchuk's ideas. Gary Vaynerchuk primarily focused on impersonal topics and informative functions, delivering facts and information to his audience while maintaining an objective relationship. The use of idiosyncrasy in his speech may be due to his fresh and inspiring ideas about business opportunities in technology, and the fact that many swear-words are aimed at himself.